Analisis Kemampuan Penalaran Siswa SMP dalam Memecahkan Masalah Matematika Berdasarkan Jenis Gaya Belajar - Oktaviana, Devi; Maimunah, Maimunah; Roza, Yenita (Jurnal Paedagogy, 2022)
This study aims to analyze the reasoning ability in solving a mathematical problem by looking at the type of student learning style. This study uses a qualitative descriptive research method. The subjects were six students of SMP Kudus Pekanbaru class VII. The research instrument was in the form of a description of two questions, a learning style questionnaire, and interviews. The learning style questionnaire instrument consists of students' positive and negative sentence questions. Then, the selection of subjects with the visual learning category was taken from three students who were seen with high, medium, and low cognitive scores. After that, based on the cognitive scores, the three students were tested through a written test regarding problem-solving to see their reasoning abilities. Moreover, the three students would also be interviewed to obtain additional information—at a medium level. Based on the indicators of mathematical reasoning, the best statements are visual learning style, and the ability to propose the best guess is the auditory learning style. Performing mathematical manipulations, the three learning styles have done quite well, and the ability to find mathematical patterns to make the best generalization is the kinesthetic learning style. The best manipulation ability is the visual learning style. Checking the validity of an argument and drawing conclusions is the best in auditory learning.